pH Changes Have a Profound Effect on Gene Expression, Hydrolytic Enzyme Production, and Dimorphism in Saccharomycopsis fibuligera - Farh, Mohamed El-Agamy; Abdellaoui, Najib; Seo, Jeong-Ah (Frontiers in Microbiology, 2021)
Saccharomycopsis fibuligera is an amylolytic yeast that plays an important role within nuruk (a traditional Korean fermentation starter) used for the production of makgeolli (Korean rice wine), which is characterized by high acidity. However, the effect of pH change (neutral to acidic) on the yeast cell to hyphal transition and carbohydrate-hydrolyzing enzyme activities for S. fibuligera has not been investigated yet. In this study, S. fibuligera strains were cultured under the different pH conditions, and the effect on the enzyme production and gene expression were investigated. An acidic pH induced a hyphal transition from yeast cell of S. fibuligera KPH12 and the hybrid strain KJJ81. In addition, both strains showed a gradual decrease in the ability to degrade starch and cellulose as the pH went down. Furthermore, a transcriptome analysis demonstrated that the pH decline caused global expression changes in genes, which were classified into five clusters. Among the differentially expressed genes under acidic pH, the downregulated genes were involved in protein synthesis, carbon metabolism, and RIM101 and cAMP-PKA signaling transduction pathways for the yeast-hyphal transition. A decrease in pH induced a dimorphic lifestyle switch from yeast cell formation to hyphal growth in S. fibuligera and caused a decrease in carbohydrate hydrolyzing enzyme production, as well as marked changes in the expression of genes related to enzyme production and pH adaptation. This study will help to elucidate the mechanism of adaptation of S. fibuligera to acidification that occur during the fermentation process of makgeolli using nuruk.